دراسة عن التأثيرات السلبية للأزمة على واقع الغطاء الحراجي في محافظة طرطوس - جرجور، سمير (جامعة البعث, 2019)
The Effects of the Crisis on Forestry in Tartous Governate The current state of Tartous’ forestry poses a question about its near future. Due to different practices during the Syrian crisis, there is a clear deterioration of forestry because of the abuse of this genuine treasure whose priceless value many people ignore. This study shows that, during the Crisis, forestry in Tartous Governate was and still is subject to a lot of damages which are mainly caused by aggressive and careless lumbering and vandalizing, in addition to intentionally setting it on fire to use it later as agricultural lands or to get natural char caul. Many small forestry areas around some villages, as well as many forest trees, which used to surround orchards and grain fields, have lately disappeared. Also, Forestry areas all over the Governate are continuously shrinking that it is very difficult in some places to restore them to their original size because this requires a lot of effort, a great budget, and a long time.
إن الوضع الراهن الذي وصلت إليه الحراج في محافظة طرطوس يدعو للقلق حول مستقبل الغطاء الحراجي على المدى المنظور ومن خلال التطورات التي حصلت خلال سنين الأزمة والتي أدت إلى تدهور واضح للغطاء الحراجي من خلال التحديات الواضحة على هذه الثروة الحقيقية التي يجهل البعض قيمتها التي لا تقدر بثمن. من خلال هذه الدراسة تبين أن الغطاء الحراجي في محافظة طرطوس وخلال سنوات الأزمة قد تعرض ومازال إلى أضرار كبيرة تتجلى بشكل أساسي في الاحتطاب الجائر وعمليات كسر أراضي الحراج الغير مدروسة وتعرضها أيضا للحرائق بفعل مقصود للاستفادة لاحقا منها كأراضي زراعية أو من مادة الفحم النباتي المستخدمة بكثرة كوقود للنراجيل التي شاع استخدامها بكثرة في السنوات الأخيرة. لقد حدث اختفاء الكثير من التجمعات الحراجية الصغيرة التي كانت منتشرة حول بعض المناطق والقرى إضافة إلى اختفاء الكثير من الأشجار الحراجية التي كانت تنمو منفردة على أطراف الحقول المزروعة ببعض الأشجار المثمرة والخضروات بالإضافة إلى تقلص المساحات الحراجية في أنحاء المحافظة بشكل مستمر بحيث أصبح من الصعب إعادة هذه الحراج إلى توازنها الأصلي في بعض مناطق المحافظة نظرا لما يتطلب ذلك من جهد كبير وأموال طائلة وزمن طويل.
Keywords: الحراج -- الغطاء الحراجي -- الرعى الجائر -- الاحتطاب -- محافظة طرطوس